Forces Influencing the American Labor Movement, Past, Present and Future - Stieber, Jack (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1968)
It seems appropriate for students of industrial relations to look back on the events of the last thirty years to see what where the major influences shaping the labor movement over this time and to look ahead a decade or so and speculate on the major issues which will have to be faced by labor in the foreseeable future.